Integrating Islamic Social Finance and Sustainable Development: A Critical Analysis of Sahal Mahfudh’s Zakat Paradigm - Muhammad Aziz (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Despite the significant growth of Islamic Social Finance (ISF) globally, zakat management often remains trapped in a legal-formalistic and charity-based paradigm, failing to address the roots of structural poverty. This study critically analyzes the Social Fiqh paradigm of KH. Sahal Mahfudh as a transformative model for integrating zakat into the Sustainable Development Goals (SDGs). Utilizing qualitative library research and a transformative hermeneutics approach, this research decodes Mahfudh’s Madzhab Manhaji methodology to reconstruct the distributive philosophy of zakat. The findings reveal that: (1) Mahfudh initiates an epistemological metamorphosis by redefining zakat from a static ritual into social engineering capital, which legitimizes systemic economic intervention; (2) the model leverages Pesantren-based social capital as a social incubator and non-financial collateral, ensuring the sustainability and accountability of the mustahiq-to-muzakki transition; and (3) the Social Fiqh paradigm serves as an indigenous epistemological bridge that aligns classical jurisprudence with SDG 1 (No Poverty) and SDG 8 (Decent Work) by targeting structural deprivations. This research contributes an indigenous sustainable development model for the global Muslim community, proving that traditional religious authority and social capital are vital for achieving holistic socioeconomic resilience in the 21st century.